2021
DOI: 10.1096/fj.202002268r
|View full text |Cite
|
Sign up to set email alerts
|

The use of fluorescence correlation spectroscopy to monitor cell surface β2‐adrenoceptors at low expression levels in human embryonic stem cell‐derived cardiomyocytes and fibroblasts

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…In HEK293 T cells, the endogenous expression of β 2 ‐adrenoceptors is extremely low, and we have previously shown that β 2 ARs tagged with an N‐terminal SNAP label under endogenous promotion are not detectable by standard confocal microscopy in CRISPR/Cas9 genome‐edited HEK293 T cells (Figure ) 35 . To confirm this low level of expression, we used CRISPR/Cas9 genome editing to incorporate an N‐terminal NLuc tag to the β 2 AR under endogenous promotion as we have described previously 32 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In HEK293 T cells, the endogenous expression of β 2 ‐adrenoceptors is extremely low, and we have previously shown that β 2 ARs tagged with an N‐terminal SNAP label under endogenous promotion are not detectable by standard confocal microscopy in CRISPR/Cas9 genome‐edited HEK293 T cells (Figure ) 35 . To confirm this low level of expression, we used CRISPR/Cas9 genome editing to incorporate an N‐terminal NLuc tag to the β 2 AR under endogenous promotion as we have described previously 32 .…”
Section: Resultsmentioning
confidence: 98%
“…β 2 ARs are also known to have a propensity to form dimers and higher order oligomers 47 . To maintain the normal cellular context, we have recently used CRISPR/Cas9‐mediated homology‐directed repair to insert both luminescent and fluorescent tags onto the N‐terminus of GPCRs into the endogenous genome, where their expression is regulated by endogenous promoters 30‐32,35 . In the present manuscript, we have investigated the utility of highly selective fluorescent ligands based on the β 2 AR selective antagonist ICI 118,551 33 in combination with CRISPR/Cas9 genome editing to investigate ligand binding to endogenous β 2 ARs under the regulation of their native promoters in HEK293 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations